Cirkulišući sTREM-1 kao biomarker mijeloidne upale kod raka dojke: dijagnostički i prognostički značaj: sTREM-1 and Myeloid Inflammation in Breast Cancer - Zhang, Jiazhennan; Yasheng, A-da-lai-ti·; Wang, Hu; Jia, Yizhen; Ai, Xiaoye; Jinsihan, Dilixiati· (Journal of Medical Biochemistry, 2026)
Background: Reliable circulating biomarkers reflecting tumor-related immune-inflammatory activation are of increasing interest in clinical biochemistry. Triggering receptor expressed on myeloid cells-1 (TREM-1) is a key amplifier of myeloid-driven inflammatory signaling, and its soluble form (sTREM-1) can be detected in peripheral blood. However, the clinical and biochemical relevance of circulating sTREM-1 in breast cancer remains insufficiently characterized. Methods: This single-center observational study included 132 patients with treatment-naive stage I–III breast cancer, 68 patients with benign breast disease, and 60 healthy controls. Serum sTREM-1 levels were measured in fasting blood samples, together with conventional biochemical and hematological parameters, including C-reactive protein (CRP), carbohydrate antigen 15-3 (CA15-3), carcinoembryonic antigen (CEA), and derived inflammatory indices (NLR, PLR, LMR, and SII). Associations between sTREM-1 and clinicopathological features, systemic inflammatory markers, and disease-free survival (DFS) were analyzed. Diagnostic performance was evaluated using receiver operating characteristic (ROC) analysis, and prognostic value was assessed using Kaplan–Meier curves and Cox regression models. Results: Serum sTREM-1 levels were significantly elevated in patients with breast cancer compared with both benign disease and healthy controls (P<0.001). Higher sTREM-1 concentrations were associated with increased tumor burden, lymph node involvement, advanced stage, and elevated Ki-67 expression (all P<0.05). Correlation analysis demonstrated that sTREM-1 was positively associated with CRP, NLR, PLR, and SII, and inversely associated with LMR (all P<0.001), indicating a close link with systemic inflammatory activation. For differentiating breast cancer from benign breast disease, sTREM-1 showed good diagnostic performance (AUC=0.842), which further improved in combination with CA15-3 and NLR (AUC=0.889). During follow-up, elevated sTREM-1 levels were associated with significantly reduced DFS, and multivariate analysis confirmed sTREM-1 as an independent prognostic factor (HR=1.96, 95% CI: 1.01–3.80, P=0.046). Conclusions: Circulating sTREM-1 is significantly increased in breast cancer and reflects myeloid-driven immune-inflammatory activation. As a measurable serum biomarker, sTREM-1 provides clinically relevant information for both auxiliary diagnosis and prognosis evaluation. These findings support its potential application in clinical biochemistry as a noninvasive indicator of tumor-associated inflammatory responses.